Impact of the Govan SHIP case management project on emergency hospital admission and GP interactions. (13th November 2019) - Levin, K; Crighton, E
Abstract: Background: The Social and Health Integration Partnership (SHIP) project was implemented in Govan, a deprived area in Glasgow in 2015. This involved multidisciplinary teams, including GPs and social workers, identifying and supporting vulnerable patients at risk of attending A&E and GP surgeries. This study measures the impact of SHIP on A&E presentations and GP interactions. Methods: Rate of A&E presentations per 1000 population in 3 participating GP practices in Govan was compared before and after onset of the service, using segmented linear regression with 9-month pre- and 36-month post- intervention periods. Rates of GP interactions were also compared, using 21-month pre- and 36-month post- intervention periods. Rates of A&E presentations and GP interactions for practice population in Drumchapel- an area with similar rates of deprivation - were used as a control. Models included autoregressive and moving average terms, and a fourier term to adjust for seasonality. Results: Govan had a lower rate of A&E presentations than Drumchapel. A&E presentations did not change significantly over time prior to SHIP in either area. At April 2015, SHIP onset, a level change of -4.34 (-7.44, -1.24) A&E presentations per 1000 was observed in both areas, however, onset of SHIP was not associated with a reduction in level or trend in A&E presentations. Rate of interactions with GP was greater in Govan than Drumchapel prior to SHIP, increasing over time in both areas. After SHIP implementation there was a significant level change of 33.78 (19.57, 47.99) per 1000 across both areas. GP interactions in Govan however saw a further reduction of -1.48 (-2.87, -0.09) per 1000 per month. This is equivalent to SHIP being associated with an absolute reduction of 37 GP interactions per thousand and a relative reduction of 7.2% by March 2018. Conclusions: The Govan SHIP initiative was associated with no significant change in A&E presentations and some small reduction in GP interactions. Key messages: The Govan SHIP initiative was associated with no significant change in A&E presentations and a small significant reduction in GP interactions. A cost effectiveness analysis of the project is recommended, given the relatively small benefits observed.